Assessing the diversity-related professional development needs of pre-service teachers. Issue 3 (12th August 2019) - Toms, Ozalle Marie; Reddig, Kim; Jones-Fosu, Stephanie
Abstract : Purpose: The purpose of this study was to assess the diversity-related professional development needs of pre-service teachers in our college. According to a report released in 2017 by the National Center for Educational Statistics (NCES), minorities accounted for 20 per cent of all public elementary and secondary school teachers in the United States during the 2015-2016 school year. The same report noted that 51 per cent of all public elementary and secondary school students in the USA were nonwhite during the same school year. Schools will continue to become increasingly more diverse as it relates to the student population. Students of color are expected to make up 56 per cent of the student population by 2024 (Digest of Education Statistics, 2013). With the changing demographics of US schools, pre-service teachers must be prepared to teach, interact and support students and families whose cultures, beliefs and lifestyles may differ from their own. Cultural competence is having an awareness of one's own cultural identity perceptions and views about difference, and the ability to learn and build on the varying cultural and community norms of students and their families (Muñoz and Graybill, 2015). The mere presence of diverse communities on college campuses is not sufficient in promoting positive educational outcomes related to diversity (Museus, 2008 ). Design/methodology/approach: Qualitative survey research was used to assess diversity related professional development needs of pre-service teachers. Students were asked an open-ended question: 'Please list topics of diversity training that should be offered to students in the college' After the question, a text box was provided to allow respondents to provide a unique answer. This approach, as opposed to providing a list of predetermined responses to select from gave respondents the freedom to say exactly what they felt should be offered. Findings: After analyzing the 163 open-ended responses provided by students six themes emerged. The themes were offering diversity-related professional development in the areas of disability/mental illness, cultural competence/awareness, LGBTQAI+/gender, facilitating conversations about diversity, discrimination and race/ethnicity. Research limitations/implications: The sample came from one university; therefore, the results may not be generalizable to other predominantly white universities. Future research should collect data at other universities or the schools within the university system to determine the needs for other campuses. The results of such a study will always be limited in scope but they do describe the needs at the targeted University. The response rate was low, 24 per cent. The reasons for the low response rate are unclear. Other survey techniques, such as mail surveys or face-to-face meetings, may be more successful in obtaining a higher response rate. Practical implications: Teacher preparation programs should assess students' perceptions, knowledge and experiences as it relates to diversity, and survey pre-service teachers to determine gaps in the diversity training currently being offered. Diversity training must be intentional to prepare pre-service teachers to meet the demands of the diverse classroom. Social implications: Future research should aim to assess pre-service teachers' beliefs about diversity throughout the entirety of teacher preparation programs by assessing pre-service teachers in multiple classes and participants who attend independent diversity training opportunities. To address the rapid increase in cultural and ethnic diversity in education worldwide, pre-service programs should target and challenge pre-service teachers' beliefs to assure equitable education to diverse students. Originality/value: The paper that has been submitted is an original research that was conducted by the first author. The first and second authors used manual coding for data analysis.